Forty years of quality-of-life research in congenital heart disease: Temporal trends in conceptual and methodological rigor. (15th September 2015) - Bratt, Ewa-Lena; Moons, Philip
Abstract: Background: The first study on quality of life (QoL) in patients with congenital heart disease was published 40 years ago. Since then, the number of QoL articles on these patients has grown exponentially. We conducted a systematic literature review of all empirical studies on QoL in patients with congenital heart disease published since 1974, with the aim of determining the range of conceptual and methodological rigor of studies and identifying temporal trends in these parameters. Methods: PubMed, Embase, and Cinahl were searched for empirical studies addressing QoL in children, adolescents, or adults with congenital heart disease, published between January 1, 1974, and December 31, 2014. We applied 10 review criteria that were previously developed by Gill and Feinstein in 1994 and further refined by Moons et al. in 2004. Overall, 234 articles were reviewed. Results: We found slight but non-significant temporal improvements in conceptual and methodological rigor and in use of assessment methods. This indicates a trend toward a more professional and exacting approach in QoL assessments. However, the majority of articles still had substantial conceptual and methodological deficits. Furthermore, we observed that citation of the publications of Gill and Feinstein and Moons et al. in published QoL research is associated with higher quality scores, suggesting that these articles have a positive impact on conceptual and methodological caliber. Conclusion: Despite 40 years of QoL research in this field, this review shows that major weaknesses in methodological rigor remain highly prevalent, which may make QoL studies inconclusive. Graphical abstract: Highlights: Quality of life studies in congenital heart disease grew exponentially in number. Conceptual and methodological rigor improved slightly over time. Prior articles on conceptual/methodological rigor may have had a positive impact. There is a more professional approach toward the assessment of quality of life.